Short-term hydrological response of soil after wildfire in a semi-arid landscape covered by Macrochloa tenacissima (L.) Kunth. (March 2022) - Lucas-Borja, Manuel Esteban; Plaza-Àlvarez, Pedro Antonio; Uddin, S.M. Mijan; Parhizkar, Misagh; Zema, Demetrio Antonio
Abstract: A proper monitoring and management of semi-arid landscapes affected by wildfire is needed to reduce its effects on the soil hydrological response in the wet season. Despite ample literature on the post-fire hydrology in forest soils, it is not well documented how the hydrologic processes respond to changes in vegetation cover and soil properties of semi-arid lands (such as the forest and areas with sparse forests) after wildﬁre. To fill this gap, this study evaluates soil hydrology in a semi-arid soil of Central Eastern Spain dominated by Macrochloa tenacissima (a widely-spread species in Northern Africa and Iberian Peninsula) after a wildfire. Rainfall simulations were carried out under three soil conditions (bare soil, burned and soils with unburned vegetation) and low-to-high slopes, and infiltration, surface runoff and erosion were measured. Infiltration rates did not noticeably vary among the three soil conditions (maximum variability equal to 20%). Compared to the bare soil, the burned area (previously vegetated with M. tenacissima ) produced a runoff volume lowered by 27%. In contrast, in the area covered by the same species but unburned, runoff was lowered by 58%. The burned areas with M. tenacissima produced soil losses that were similar as those measured in bare soils, and, in steeper slopes, even higher. Erosion was instead much lower (−83%) in the sites with unburned vegetation. Overall, the control of erosion in these semi-arid lands is beneficial to reduce the possible hydrological effects downstream of these fire-prone areas. In this direction, the establishment of vegetation strips of M. tenacissima in large and steep drylands of bare soil left by fire may be suggested to land managers. Highlights: Soil hydrology in a semi-arid soils dominated by Macrochloa tenacissima is evaluated. Infiltration rates did not noticeably vary among soils. Compared to bare soils, runoff decreased in both burned and unburned sites. Erosion was similar in bare and burned soils, and lower in unburned sites. M. tenacissima strips in drylands are suggested as post-fire management.